Estudio de factibilidad para la producción de morrales para ciclistas, en la empresa Industrias Talu Ltda de la ciudad de Bogotá (2017)
With the help of the company and the data allowed by it, this study is carried out, making a diagnosis of how Colombia and Bogota in matters of politics, economy, social, technology, environmental and legal, thus know the manufacturing industry as it develops in the country. Developing this work studies are made pertinent for the correct development of the product and the development of the company, a market study was developed where it is possible to obtain information of the users of the bicycle if it is a pleasant product for them, a technical study where Evidence that does not affect any production process of the company, an administrative study that provides a structure for the development of objectives and goals and finally a financial study that allowed us to know with an internal rate of opportunity (TIO) of 20%.